No Difference in Hip Muscle Volumes and Fatty Infiltration in Those With Hip-Related Pain Compared to Controls - Timothy H Retchford; Kylie J Tucker; Harvi F Hart; Adam I Semciw; Patrick Weinrauch; Alison Grimaldi; Sallie M Cowan; Kay M Crossley; Joanne L Kemp (International Journal of Sports Physical Therapy)
# Background